HIV infection. Opportunistic infections - Ryabokon, E. V.; Ushenina, N. S.; Furyk, E. A.; Savelyev, V. G.; Mashko, O. P.; Zadiraka, D. A.; Рябоконь, Олена Вячеславівна; Ушенiна, Нiна Степанiвна; Фурик, Олена Олександрівна; Савельєв, Валерій Григорович; Машко, Оксана Павлівна; Задирака, Денис Анатолійович (Zaporozhye state medical university, 2016)
In the manual reveals issues of modern concepts of etiology, pathogenesis, classification, clinical manifestations, specific diagnosis, treatment and prevention of HIV. The manual for English students of 5, 6 courses of medical faculty.